Evaluating the Impact of Surgeon Self-awareness by Comparing Self Versus Peer Ratings of Surgical Skill and Outcomes for Bariatric Surgery. Issue 1 (12th July 2022) - Varban, Oliver A.; Thumma, Jyothi R.; Carlin, Arthur M.; Ghaferi, Amir A.; Dimick, Justin B.; Finks, Jonathan F.
Abstract : Objective: To evaluate variation in self versus peer-assessments of surgical skill using surgical videos and compare surgeon-specific outcomes with bariatric surgery. Summary Background Data: Prior studies have demonstrated that surgeons with lower peer-reviewed ratings of surgical skill had higher complication rates after bariatric surgery. Methods: This is a retrospective cohort study of 25 surgeons who voluntarily submitted a video of a typical laparoscopic sleeve gastrectomy (SG) between 2015 and 2016. Videos were self and peer-rated using a validated instrument based on a 5-point Likert scale (5= "master surgeon" and 1= "surgeon-in-training"). Risk adjusted 30-day complication rates were compared between surgeons who over-rated and under-rated their skill based on data from 24, 186 SG cases and 12, 888 gastric bypass (GBP) cases. Results: individual overall self-rating of surgical skill varied between 2.5 and 5. Surgeons in the top quartile for self:peer ratings (n = 6, ratio 1.58) had lower overall mean peer-scores (2.98 vs 3.79, P = 0.0150) than surgeons in the lowest quartile (n = 6, ratio 0.94). Complication rates between top and bottom quartiles were similar after SG, however leak rates were higher with gastric bypass among surgeons who over-rated their skill with SG (0.65 vs 0.27, P = 0.0181). Surgeon experience was similar between comparison groups. Conclusions and Relevance: Self-perceptions of surgical skill varied widely. Surgeons who over-rated their skill had higher leak rates for more complex procedures. Video assessments can help identify surgeons with poor self-awareness who may benefit from a surgical coaching program.